Ethanolic extract of Caesalpinia bonduc seeds triggers yeast metacaspase-dependent apoptotic pathway mediated by mitochondrial dysfunction through enhanced production of calcium and reactive oxygen species (ROS) in Candida albicans - Sasidharan, Shan; Nishanth, Kumar S.; Nair, Hareendran J. (Frontiers in Cellular and Infection Microbiology, 2022)
Candida albicans is a widespread disease-causing yeast affecting humankind, which leads to urinary tract, cutaneous and various lethal systemic infections. As this infection rate steadily increases, it is becoming a significant public health problem. Recently, Caesalpinia bonduc has received much attention from researchers due to its diverse pharmacological properties, including antimicrobial effects. Accordingly, we first planned to explore the in-vitro anticandidal potential of three extracts obtained from C. bonduc seeds against four Candida species. Initially, the anticandidal activity of the seed extracts was checked by the microdilution technique. Out of three seed extracts tested, ethanolic extract of C. bonduc seed (EECS) recorded the best activity against C. albicans. Hence, we next aimed to find out the anticandidal mechanism of EECS in C. albicans. The liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QTOF-MS) analysis showed that the major compounds present in the EECS were tocopherols, fucosterol, linoleic acid, β-amyrin, β-sitosterol, campesterol, cassane furanoditerpene, Norcassane furanoditerpene and other diterpenes. To evaluate the cell death mechanism in C. albicans, a series of parameters related to apoptosis, viz., reactive oxygen species (ROS) production, membrane permeability, mitochondrial membrane potential, release of cytochrome c, DNA fragmentation, nuclear condensation, increased Ca2+ level in cytosolic and mitochondrial and activation of metacaspase, were analyzed. The results showed that EECS treatment resulted in the elevation of ROS, which leads to plasma membrane permeability in C. albicans. Annexin V staining further confirms the early stage of apoptosis through phosphatidylserine (PS) externalization. We further inspected the late apoptotic stage using DAPI and TUNEL staining assays. From the results, it can be concluded that EECS triggered mitochondrial dysfunction by releasing high levels of ROS, cytochrome c and Ca2+resulting in the activation of metacaspase mediated apoptosis, which is the central mechanism behind the cell death of C. albicans. Finally, a Galleria mellonella-C. albicans infection system was employed to assess the in-vivo potential of EECS. The outcomes displayed that the EECS considerably enhanced the recovery rate of G. mellonella larvae from infection after the treatment. Additionally, EECS also recorded low hemolytic activity. This study thus spotlights the anticandidal potential and mechanism of action of EECS against C. albicans and thus delivers a promising treatment approach to manage C. albicans infection in the future.